Art's Passing for Hegel, Lacoue-Labarthe, and Nancy. Issue 3 (4th July 2021) - McKeane, John
Abstract: This article explores the understanding of æsthetics in the work of Philippe Lacoue-Labarthe and Jean-Luc Nancy. It does so in relation to Hegel's claim about art's dissolution or passing at the end of the classical Greek age, as the world entered the modern Christian age. For the two French thinkers, their relation to Hegel (and to a large extent æsthetics generally) turns on the claim that art was, but is not. The article looks first at Nancy's discussion of the young girl carrying fruit, a figure used by Hegel to depict this scene in the history of spirit, then moves on to a rarely read but significant article by Lacoue-Labarthe, "The Unpresentable, " before some final thoughts.